Teknologi Finansial dan Sistem Informasi Manajemen (Tinjauan Tren, Isu, dan Arah Masa Depan): (Studi Systematic Literature Review) - Jely Suryani; Hamdani Hamdani (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2026)
This study aims to analyse the development of Financial Technology (FinTech) and Management Information Systems (MIS), implementation challenges, and their role in supporting digital transformation in the financial sector. This study employs the Systematic Literature Review (SLR) method by reviewing Scopus-indexed articles published between 2020 and 2026. The PRISMA framework was applied to ensure a systematic and transparent article selection process, resulting in 37 relevant articles selected for further analysis. The findings reveal that Financial Information Systems and FinTech significantly contribute to improving operational efficiency, financial transparency, strategic decision-making quality, risk management, and financial inclusion. Furthermore, the integration of emerging technologies such as Artificial Intelligence (AI), blockchain, machine learning, big data analytics, cloud computing, Internet of Things (IoT), and cybersecurity strengthens the effectiveness of digital financial systems in modern organisations. Bibliometric analysis using VOSviewer also demonstrates that fintech has become the central theme interconnected with cybersecurity, banking, sustainability, investment, and innovation studies. Despite these benefits, the implementation of FinTech and MIS still faces several challenges, including cybersecurity risks, data privacy issues, regulatory limitations, digital literacy gaps, and infrastructure readiness. This study contributes theoretically by mapping research trends and identifying future research opportunities, while practically providing insights for organisations in developing adaptive, secure, and sustainable digital financial systems. Future research is recommended to develop predictive and intelligent financial information system models based on AI and blockchain technologies to address increasingly complex business dynamics.